Analysts' and Investors' Reactions to Consistent Earnings Signals. (27th November 2015) - Caylor, Marcus L.; Christensen, Theodore E.; Johnson, Peter M.; Lopez, Thomas J.
Abstract: We investigate (1) whether the trajectory of the current‐quarter earnings expectation path (defined by the signs of the forecast revision and the earnings surprise) provides information about future firm performance, and (2) the extent to which analysts and investors react to that information. Our results indicate that analysts underreact more to earnings information revealed by consistent‐signal earnings expectation paths than to earnings information communicated by inconsistent‐signal expectation paths. We also find that the current earnings expectation path provides incremental explanatory power for future abnormal returns, even after controlling for the sign and magnitude of the earnings surprise. Overall, our evidence is consistent with underreaction stemming from analysts' and investors' bias in processing the information in consistent‐signal earnings expectation paths.